Satellite-Based Land Surface Temperature Estimation of Bogor, Indonesia - Ema Kurnia; I Nengah Surati Jaya; Widi Atmaka (Indonesian Journal of Electrical Engineering and Computer Science, 2016)
The earth’s average temperature has been a big issue on the global warming. The warming of the earth is largely the results of emission of carbon dioxide and other greenhouse gasses (GHG) from human activities. As a hinterland of the Capital City, in the last two decades, Bogor is also getting warmer in comparison with the previous decades. This paper presents how the land surface temperature (LST) had been estimated using Split-Window (SW) algorithm and how its spatial distribution in Bogor was computed. The spectral radiance of Landsat-8 TIR bands 10 and 11, the emissivity values, and water vapor used as the input on SW Algorithm. The study revealed that the temperature within the built-up area, have warmer temperature than their surrounding ranging from 400C to 450C of 3,403.9 ha. The use of SW algorithm is quite reliable and accurate to estimate the LST derived from Landsat-8 having a mean deviation of only 2.7%, less than standard acceptable of 10%.